북부 양산단층 영해지역 단층암에 기록된 미끌림감각 반전 - 이하경; 한래희; 천영범; Hakyung Lee; Raehee Han; Youngbeom Cheon (자원환경지질, 2024)
The Yangsan Fault is known to have experienced kinematic changes due to tectonic stress variations since its formation in the Late Cretaceous. However, direct kinematic evidence based on the microstructure of fault rocks is rare. In this study, we analyzed the fault rocks of the Yangsan Fault using core samples collected from Yeonghae-eup, Yeongdeok-gun, in Southeast Korea, and aimed to obtain kinematic information through observations of rock slab-scale and micro-scale structures. In the inclined core samples with a length of 73.2 meters, fault rocks appear over a width of approximately 25 meters, consisting of foliated cataclasite derived from gneiss and foliated gouge derived from sedimentary rock. Rock slab-scale observations revealed dextral shear deformation in the cataclasite and sinistral shear deformation in the fault gouge. Micro-scale observations identified a principal slip zone approximately 1 mm wide, along which three units with different foliation orientations were found, indicating a dextral-sinistral-dextral sequence of slip sense changes. These findings provide geological evidence of slip-sense reversals in the northern segment of the Yangsan Fault, alongside similar reversals observed in the Bogyeongsa area, Pohang, approximately 30 km from the study area, and the identified sequence of slip senses is crucial for establishing the kinematic history of the Yangsan Fault. 양산단층은 백악기 후기에 형성된 이후 현재까지 조구조적 응력 변화에 따라 운동학적 특성이 변화해 왔다고 알려져 있으나, 단층암의 미세구조에 기록된 운동학적 증거를 제시한 연구는 드물다. 본 연구에서는 영덕군 영해읍에서 수집된 코어시료를 대상으로 단층암 내 암판규모(rock slab-scale) 구조 및 미세구조를 관찰함으로써 영해지역 양산단층의 운동학적 정보를 파악하였다. 총 73.2 m 길이의 경사시추 코어시료 중 약 25 m 폭에 걸쳐 단층암이 나타나며, 이는 편마암 기원의 엽리상 파쇄암과 퇴적암 기원의 엽리상 단층비지로 구성된다. 암판규모 구조 관찰에서는 파쇄암에서 우수향, 단층비지에서는 좌수향의 전단변형이 확인되었다. 미세구조 관찰에서는 약 1 mm 폭의 주미끌림대를 따라 우수향-좌수향-우수향 순으로 미끌림감각이 변하였음을 지시하는 세 영역이 발견되었다. 이 결과는 본 연구지역에서 약 30 km 떨어진 포항 보경사지역에서의 미끌림감각 반전과 함께 양산단층 북부분절의 운동학적 변화에 대한 지질학적 증거를 제공하며, 본 연구에서 확인된 미끌림감각의 순서는 양산단층의 운동사 수립에 중요하다.